Perbedaan Jumlah Leukosit Pasien Apendisitis Akut dan Perforasi - Akhmad Kheru; Ni Putu Sudiadnyani; Puji Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Background: Appendicitis is defined as inflammation of the vermiform appendix (worm bag) which is the most common emergency surgery in children and young adults with abdominal pain. Appendicitis is thought to be caused by obstruction of the appendix lumen by faecalith, fecal stasis, lymphoid hyperplasia or caecal neoplasm, and various infections by pathogens. Appendicitis occurs more in men than in women with a ratio of 1:4 events and strikes at an average age of 10 to 30 years. Aims: Knowing the comparison of the number of leukocytes in patients with acute appendicitis and appendicitis with perforation. Method: This type of research is quantitative with observational analytical research design with a cross-sectional approach. Data retrieval uses secondary data by looking at the number of leukocytes in the respondent's medical record. Bivariate analysis with the Non-parametric Man-Whitney test. Results: It is known from the analysis of data on the number of acute appendicitis leukocytes as many as 50 people and Perforation Appendicitis as many as 42 people. Conclusion: There is a significant difference in the number of leukocytes of the Acute Appendicitis group with Perforated Appendicitis.